2018
DOI: 10.1245/s10434-018-6383-z
|View full text |Cite
|
Sign up to set email alerts
|

Single-Axillary-Incision Endoscopic-Assisted Hybrid Technique for Nipple-Sparing Mastectomy: Technique, Preliminary Results, and Patient-Reported Cosmetic Outcome from Preliminary 50 Procedures

Abstract: The proposed single-axillary-incision endoscopic hybrid technique for nipple-sparing mastectomy was a safe procedure with low morbidity and associated with high patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 29 publications
0
46
0
Order By: Relevance
“…New and less invasive approaches are currently being evaluated. For example, a single-axillary-incision endoscopic hybrid technique was safe and associated with low morbidity and high patient satisfaction in an early patient series from Taiwan [ 40 ]. This hidden incision type can also be used for robotic assisted techniques that have the potential to further improve patient satisfaction although these techniques are not widely practiced at present [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…New and less invasive approaches are currently being evaluated. For example, a single-axillary-incision endoscopic hybrid technique was safe and associated with low morbidity and high patient satisfaction in an early patient series from Taiwan [ 40 ]. This hidden incision type can also be used for robotic assisted techniques that have the potential to further improve patient satisfaction although these techniques are not widely practiced at present [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…As consequence, the recent trends are to move the access far from the breast footprint in the search for the ideal incision for NSM. [5][6][7][8][9][10][11][12] We believe that the ideal NSM incision is the axillary one as this single access allows to perform a safe nonendoscopic mastectomy in cup A and B breasts, sentinel node biopsy/axillary clearance, and nonendoscopic immediate prepectoral reconstruction when feasible (ie thick skin flaps) or endoscopic submuscular-subfascial direct-toimplant reconstruction, with the main advantage of a hidden and well-concealed scar. In our experience, a 6-cm incision located on the lowest axillary fold along the mid-axillary line allows to perform a safe nonendoscopic mastectomy, node surgery, and direct-to-implant reconstruction both submuscular and prepectoral.…”
Section: Discussionmentioning
confidence: 99%
“…With the help of endoscopic technique, NSM can be performed through a single axillary incision made for axillary surgery, which is able to significantly minimize the scarring on the breast (endoscopic nipple sparing mastectomy, ENSM technique). Lai et al [19] reported their preliminary results of ENSM, suggesting its oncological safety while Du et al [20] reported in a prospective non-randomized study that patients who underwent ENSM were more satisfied with their cosmetic outcomes as compared to those who underwent the traditional BCS.…”
Section: Scarless Strategy In Volume Replacement Approachmentioning
confidence: 99%